2007
DOI: 10.1097/wno.0b013e31815b9f67
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Ischemic Optic Neuropathy After Minimally Invasive Prostatectomy

Abstract: Two patients developed postoperative ischemic optic neuropathy (ION) after laparoscopic radical prostatectomy. One operation was robotically assisted; the other was performed with the conventional laparoscopic technique. These new minimally invasive techniques offer many advantages, but they require steep supine head-flexed (Trendelenburg) positioning. Until they are mastered by surgeons, operative times may be prolonged beyond those associated with the traditional technique. As a result, ION may occur more fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(96 citation statements)
references
References 8 publications
2
91
0
3
Order By: Relevance
“…Cases of visual impairment have been reported to occur in minimally invasive proctocolectomy, laparoscopic nephrectomy and robotic prostatectomy [45][46][47][48] . During robotic prostatectomy, increased intraocular pressure occurs due to prolonged duration in steep Trendelenburg position combined with CO2 insufflation of the abdomen.…”
Section: Perioperative Visual Loss In Other Surgeriesmentioning
confidence: 99%
“…Cases of visual impairment have been reported to occur in minimally invasive proctocolectomy, laparoscopic nephrectomy and robotic prostatectomy [45][46][47][48] . During robotic prostatectomy, increased intraocular pressure occurs due to prolonged duration in steep Trendelenburg position combined with CO2 insufflation of the abdomen.…”
Section: Perioperative Visual Loss In Other Surgeriesmentioning
confidence: 99%
“…16 Beyond the obvious concern of preserving overall metabolic homeostasis and optimal brain perfusion, maintaining an acceptable PE 0 CO 2 tension is therefore imperative to minimize the risk of serious ocular consequences, such as complete bilateral visual loss. 17 Whereas PE 0 CO 2 monitoring has proven to be an acceptable alternative to arterial blood gas PCO 2 in many clinical circumstances, the utility of PE analysis is a sufficient guide for the management of the ventilation strategy in this clinical setting. We found that the arterial-to-PE 0 CO 2 tension difference of 1.06 kPa in the supine position increased to a maximum of 1.41 kPa after 2 h in the Trendelenburg position and tended to decrease back to normal pre-Trendelenburg values thereafter.…”
mentioning
confidence: 99%
“…However, more recently, it was found that prolonged steep Trendelenburg and pneumoperitoneum was tolerated well and that regional cerebral oxygenation was preserved in male patients undergoing Robotic-assisted laparoscopic radical prostatectomies [20]. Other risks of steep Trendelenburg also involve possible injury to the eye, even blindness, as intraocular pressures are elevated for long durations of robotic-assisted MIS [21] [22]. The elderly are at an increased risk as they have a higher incidence of pre-existing eye disease.…”
Section: Discussionmentioning
confidence: 99%